ANALISIS FAKTOR PRODUKSI, DAN PENDAPATAN USAHATANI PADI SAWAH - Harumbaha, Febriyani M.S.; Kapa, Maximillian M.J.; Nainiti, Selfius P.N. (Undana Press, 2023)
This study aims to determine the production, and income factors of rice farming in the Oesao village , East Kupang District, Kupang Regency. The determination of the research location was carried out purposively (purposive sampling), namely in the Oesao Village, East Kupang District, Kupang Regency. The sample in the study were 38 rice farmers. The data analysis used was multiple linear regression analysis, revenue analyis, and income analysis. The results showed that the factor that significantly influenced the production of rice was land area, while the other four factors had no significant effect. Simultaneously all factors have a very significant effect on lowland rice production with a very significant value of 0,00<0,05. As well as 89% of the influence of land area, seeds, fertilized, pesticides and labor on lowland rice production can be explained by the variables in the model (LnY= 2,599+ 2,362LnX1- 0,320LnX2+ 0,072LnX3- 0,066LnX4- 0,029LnX5). With an average income of paddy rice farming per respondent farmer of IDR 8.842.256 per average land area of 72 acres in one growing season.